A review of all-optical photoacoustic spectroscopy as a gas sensing method. Issue 2 (7th February 2021) - Yang, Tianhe; Chen, Weigen; Wang, Pinyi
Abstract: Photoacoustic spectroscopy (PAS) is an ultrasensitive method for gas sensing, which usually using a capacitive microphone as a signal detector. However, the electric nature of the microphone limits their applications in the circumstances with high temperature, electromagnetic interference (EMI), as well as explosive environments. Due to the uncharged and high-sensitivity characteristics, optical acoustic sensor is an ideal substitute in the circumstances above. Thus, all-optical PAS can get better applications in a harsh environment. In this paper, a brief review of all-optical PAS used in gas sensing with different optical acoustic sensing technologies is presented, such as intensity-modulated technology, fiber Bragg grating (FBG)-based technology, and interferometer-based technology. Besides, using a fiber-optic photoacoustic (PA) sensor would allow the realization of remote detection, in-situ detection, real-time monitoring, and multiplexed multi-point detection within a fiber-optic network. Finally, the advantages and limitations of these different technologies are discussed.